2007
DOI: 10.1002/ird.282
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of water storage capacity in wetland rice fields through deepwater management practice

Abstract: Paddy field storage of rainfall by bunds is like a rainwater cistern system during the rainy season. Deepwater management practice in paddy fields might be good for rice production and water storage capacity at the same time. The study was conducted in an experiment testing two water management treatments with six rice variety treatments using two lysimeter experiments.The results revealed that deepwater management significantly affected rice production. On the other hand, deepwater management increased the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
0
10
0
2
Order By: Relevance
“…A altura da lâmina de água nesses dois tratamentos na maior parte do período experimental foi menor que no tratamento com irrigação contínua (Figura 1), ficando assim uma borda livre (diferença entre a altura da lâmina de água e a da taipa), que proporciona o armazenamento de água da chuva no interior da parcela, reduzindo assim o extravasamento. Esses resultados corroboram os estudos realizados por Watanabe et al (2006Watanabe et al ( , 2007, Chang et al (2007) e Phong et al (2008.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A altura da lâmina de água nesses dois tratamentos na maior parte do período experimental foi menor que no tratamento com irrigação contínua (Figura 1), ficando assim uma borda livre (diferença entre a altura da lâmina de água e a da taipa), que proporciona o armazenamento de água da chuva no interior da parcela, reduzindo assim o extravasamento. Esses resultados corroboram os estudos realizados por Watanabe et al (2006Watanabe et al ( , 2007, Chang et al (2007) e Phong et al (2008.…”
Section: Resultsunclassified
“…Neste último tipo de perda de água podem estar contidos agrotó-xicos na solução e/ou adsorvidos a coloides do solo em suspensão (Watanabe et al, 2006(Watanabe et al, , 2007Chang et al, 2007;Phong et al, 2008), promovendo maior risco de contaminação ambiental. Trabalhos recentes sobre o monitoramento da qualidade de água identificaram contaminações de fontes superficiais em diferentes regiões orizícolas do Estado do Rio Grande do Sul (Silva et al, 2009): região central (Bortoluzzi et al, 2006Marchezan et al, 2007) e região sul (Grutzmacher et al, 2008).…”
Section: Introductionunclassified
“…In this scheme, irrigation water is supplied in appropriate quantities at the ideal time and in the proper order to ensure that all rice paddies receive their minimum water requirements; for example, during 5-to 8-day periods, a total of 6-8 cm water is supplied to the rice paddies only on the first day (Chen and Liu 2002). Chang et al (2007) proposed an irrigation scheme called deepwater management practice for soil and water conservation. Deepwater management practice is applied during the panicle- formation stage, by increasing the maximum water depth to 25 cm.…”
Section: Discussionmentioning
confidence: 99%
“…However, Taiwan is plagued with water scarcity problems as fresh water for irrigation is limiting rice production. Rapid urbanization and industrialization along with high irrigation water consumption from the agriculture sector (80%) have been major contributing factors [9]; furthermore, this situation is exacerbated by climate change. In 2014, rice production was compromised as a Madagascar, a comparison over five years found that SRI was labor saving by year four compared to years one to three [32].…”
Section: Introductionmentioning
confidence: 99%